2016
DOI: 10.1111/jav.00853
|View full text |Cite
|
Sign up to set email alerts
|

Chemical labels differ between two closely related shearwater taxa

Abstract: Chemical signals may be the basis of interspecifi c recognition and speciation in many animals. To test whether a chemical label allowing recognition between closely related species exists in seabirds, we investigated two closely related taxa breeding sympatrically at some localities: Cory ' s and Scopoli ' s shearwaters. Procellariiform seabirds are ideal for this study because they have a well-developed olfactory system and unequalled associated capabilities among birds. We analysed and compared the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 108 publications
(180 reference statements)
0
9
0
Order By: Relevance
“…In numerous avian species, the chemical composition of preen oil encodes information on various bird characteristics, such as sex, age, individuality, seasonal variation, species affiliation or genotype (Hagelin 2007, Mardon et al 2010, Wyatt 2014, Caro et al 2015, Gabirot et al 2016, Krause et al 2018. Although the biological meaning of these differences has rarely been investigated, a few studies have shown that most of these odour cues can be recognized by birds Nevitt 2004, Mardon andBonadonna 2009) and influence social behaviour (Balthazart and Schoffeniels 1979, Hirao et al 2009, Caspers et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In numerous avian species, the chemical composition of preen oil encodes information on various bird characteristics, such as sex, age, individuality, seasonal variation, species affiliation or genotype (Hagelin 2007, Mardon et al 2010, Wyatt 2014, Caro et al 2015, Gabirot et al 2016, Krause et al 2018. Although the biological meaning of these differences has rarely been investigated, a few studies have shown that most of these odour cues can be recognized by birds Nevitt 2004, Mardon andBonadonna 2009) and influence social behaviour (Balthazart and Schoffeniels 1979, Hirao et al 2009, Caspers et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by Leclaire et al (2011) in black‐legged kittiwakes Rissa tridactyla during the bird breeding season. However, the composition of the uropygial gland secretion did not differ between sexes in other species, such as crested auklet (Hagelin et al 2003) and Cory's and Scopoli's shearwaters (Gabirot et al 2016). In addition, non‐significant differences between sexes were found in the composition of the volatile fraction of uropygial gland secretions of juvenile house sparrows (Díez‐Fernández et al 2020a), further suggesting that sexual differences may be only apparent in adult/sexually mature birds.…”
Section: Discussionmentioning
confidence: 97%
“…The composition of this secretion varies among species (Haribal et al 2009) and age classes (Shaw et al 2011) and may differ between sexes (Whittaker et al 2010). Sexual differences in the composition have been detected in some species such as Bengalese finches Lonchura striata (Zhang et al 2018) and dark‐eyed juncos Junco hyemalis (Soini et al 2007), but not in others, such as crested auklets Aethia cristatella (Hagelin et al 2003), Cory's shearwaters Calonectris borealis and Scopoli's shearwaters C. diomedea (Gabirot et al 2016). The uropygial secretion contributes to a large extent to bird odour (Moreno‐Rueda 2017), and differences in its composition may therefore play an important role in bird intraspecific and interspecific communication (Caro et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although sexual dimorphism in chemical cues from feathers or preen secretions has been reported in several bird species (Amo et al 2012;Leclaire et al 2011;Whittaker et al 2010;Zhang et al 2010), it is not ubiquitous. For instance, king penguins (Aptenodites patagonicus) and Cory's shearwaters (Calonectris borealis) seem to exhibit no sex-differences in scent (Gabirot et al 2018;Gabirot et al 2016). Pigeons display sexual polymorphism in iridescent coloration of neck feathers (Chatelain et al 2017;Leclaire et al 2014a), and might, therefore, use this other trait to discriminate between sexes.…”
Section: Discussionmentioning
confidence: 99%